Influence of a Non-ionic Surfactant on the Release of Rhodamine B from Poly(vinyl) Alcohol/Polyoxalate/Span-80 Composite Nanofibers Prepared by Emulsion Electrospinning - Nutthakritta Phromviyo; Apiwat Chompoosor; Saowapak Teerasong (My University, 2023)
Controlling drug release using a nanocomposite method is crucial; however, burst release must be avoided in order to obtain effective controllable drug release. In this study, poly(vinyl) alcohol/polyoxalate/Span-80 (PVA/ POX/ Span-80) composite nanofibers loaded with Rhodamine B were produced using emulsion electrospinning. The objective of this work was to evaluate the cooperative roles of POX and Span-80 on nanofibrous scaffold stability and drug release regulation by monitoring Rhodamine B release performance from electrospun composite nanofibers. The microstructure and hydrophilic properties of the emulsion electrospun nanofibers were studied using scanning electron microscopy (SEM), water contact angle, and swelling tests. According to the results, increasing the POX content had a significant effect on the size of nanofibers. The water contact angles increased as the POX content increased. The release of Rhodamine B was governed by a two-stage diffusion mechanism that was greatly influenced by PVA/POX ratios and Span-80. To compare release behavior, non-emulsion electrospun nanofibers without Span-80 were prepared as control samples. Emulsion nanofibers were found to release at a slower rate than non-emulsion nanofibers. The in vitro release profiles revealed that Rhodamine B was released from emulsion electrospun fibers in a sustainable manner and that no initial burst release was observed. These findings imply that emulsion electrospun nanofibers can potentially be used to deliver drugs, nutraceuticals, and fragrances in a prolonged manner
Keywords: Electrospinning; Vinyl alcohol; Rhodamine B; Polyvinyl Alcohol; Rhodamine; Electrospun Nanofibers in Biomedical Applications